Quality of life of women using the etonogestrel long-acting reversible contraceptive implant after abortion for unplanned pregnancy. (3rd July 2020) - Caruso, Salvatore; Vitale, Salvatore Giovanni; Fava, Valentina; Pasqua, Salvatore Di; Rapisarda, Agnese Maria Chiara; Cianci, Stefano
Abstract: Objectives: The aims of the study were to investigate the effect of a subcutaneous etonogestrel-containing contraceptive implant on the quality of life (QoL) and sexual function of women who had undergone termination of an unplanned pregnancy. Methods: At pregnancy termination 140 women received contraceptive counselling on the etonogestrel implant. The Short Form-36 questionnaire, the Female Sexual Function Index and the Female Sexual Distress Scale were used to investigate, respectively, the QoL, sexual function and sexual distress of the women at baseline and at 6, 12, 24 and 36 months of follow-up. Results: The study group comprised 86 (61.4%) women who chose to use the contraceptive implant. The control group comprised 28 (20.0%) women who chose to use short-acting reversible contraception (SARC) and 26 (18.6%) women who chose not to use hormonal contraception. In the women not using hormonal contraception there were 23 (88.5%) unintended pregnancies before the end of the 3 year study period. QoL, sexual function and sexual distress improved in the study group from the 6 months follow-up until the end of the study ( p  < 0.001). QoL ( p  < 0.02) and sexuality ( p  < 0.001) gradually improved in the control group after 24 and 12 months of follow-up, respectively. None of the women using the etonogestrel implant became pregnant during the study. Inter-group analysis showed better improvement in QoL, sexual function and sexual distress in the study group than in the control group from 6 months ( p  < 0.004) until the end of the study ( p  < 0.001). Conclusion: Compared with SARC and non-hormonal contraception, the contraceptive implant promoted better QoL and sexuality in users and reduced the incidence of unplanned pregnancy. However, the women who opted for SARC or non-hormonal contraception did so because of the lower cost compared with that of the contraceptive implant.